The use of augmented reality in the marketing mix of physical products: Current practices and future implications - Langaro, D.; Martins, L. (Managerial challenges and social impacts of virtual and augmented reality, 2020)
The current book chapter intends to explore what are the current practices in place regarding the use of AR in the marketing mix of physical products and the implications for the future. While exploring this research question, the study contributes for identifying common aspects and drawing recommendations for future studies and practices. For addressing the research question proposed, twenty cases of physical products using AR as part of their marketing mix were identified and analysed for their characteristics. The EPI Cube framework and its contextualization in the customer experience was used as theoretical model for guiding the analysis. Findings are presented and implications for theory and practice are discussed.